Metode Penanaman Karakter Santri dan Santriwati TK dan TPA Al-Futuhiyyah Banjarmasin - Ahyar Rasyidi; Dwina Dwina (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2021)
This study seeks to reveal the method of cultivating the character of Santri and Santriwati Kindergarten/TPA Al-Futuhiyyah Banjarmasin City and its supporting and inhibiting factors. This study also aims to describe the Santri and Santriwati Character Cultivating Methods for Kindergarten/TPA Al-Futuhiyyah Banjarmasin City and find the supportive and inhibiting factors. This research method is classified as field research. At the same time, the approach used is descriptive-qualitative, namely by explaining events directly based on direct observation at the location and object of research. The subjects of this research were teaching staff. This study was the Method of Instilling the Character of Santri and Santriwati Kindergarten/TPA Al-Futuhiyyah Banjarmasin City. This study uses the method of observation, interviews, and documentation. From the results of this study, several findings were obtained that the method used by the teacher in cultivating the character of students and female students was effective through integrating knowledge and charity in daily activities. The factors that support the cultivation of character are the educational background of teachers who incidentally come from Islamic boarding schools and are pursuing an undergraduate degree at PTKIN/PTKIS in Banjarmasin, as well as a conducive family environment. Meanwhile, the inhibiting factor in cultivating character is part of the students' family environment, especially parents who are less proactive in paying attention to changes in children's attitudes, as well as the influence of association with peers, which then has a negative effect on the formation of their character.